Liquidity and congestion - Afonso, Gara (Journal of Financial Intermediation, 2011)
This paper studies the relationship between the endogenous arrival of investors to a market and liquidity in a search-based model of asset trading. Entry of investors causes two contradictory effects. First, it reduces trading costs, which attracts new investors (externality effect). But secondly, as investors concentrate on one side of the market, the market becomes “congested,” decreasing the returns to investing and discouraging new investors from entering (congestion effect). The equilibrium level of liquidity depends on which of the two effects dominates. When congestion is the leading effect, some interesting results arise. In particular, diminishing trading costs can deteriorate liquidity and welfare.